Physical, chemical, and microbiological stability study of diluted atropine eye drops - Jumpei Saito; Hitomi Imaizumi; Akimasa Yamatani (BMC, 2019)
Abstract Background Atropine eye drops are indicated for juvenile myopia progression, cycloplegia, amblyopia, and strabismus. According to the package insert, 10 mg/mL atropine eye drops must be diluted for pediatric patients to prevent systemic adverse effects. Compounding units in hospital pharmaceutical departments or community pharmacies are compelled to prepare this essential medication; however, validated atropine stability data is limited and the shelf life after preparation is extremely short. As it is a long-term treatment, a longer shelf life is necessary to improve patient care. This study aimed to demonstrate the physical, chemical, and microbiological stability of diluted atropine eye drops over a period of six months. Methods Preparation consists of dilution of a 10 mg/mL atropine solution (Nitten Atropine Ophthalmic Solution 1%; Nitten Pharmaceutical Co., Ltd.) in 0.9% NaCl to concentrations of 0.1, 1.0, 2.5, and 5.0 mg/mL, followed by a sterilizing filtration procedure and then an aseptic filling process of 5 mL in 5 mL polyethylene eyedropper bottles. The entire process is carried out in an overpressure isolator. All concentration products were kept for six months at 25 °C or 5 °C. Visual inspection was conducted and pH, osmolality, and atropine concentration were measured at day 0, day 14, day 28, and every month until six months. Atropine concentration was measured using liquid chromatography tandem mass spectrometry. The sterility was monitored using a method adapted from the Japanese Pharmacopoeia sterility assay. Results Atropine remained within ±5% of the target value in the six batches. Osmolality (285 mOsm/kg) as well as pH (5.88) were kept constant. No variations in solution characteristics (crystallization, discoloration) were noted. Sterility was maintained. Conclusions This study validated the physical, chemical, and microbiological stability of 0.1, 1.0, 2.5, and 5.0 mg/mL atropine sulfate eye drops conserved inside polyethylene eyedroppers for six months at 25 °C or 5 °C.